Impaired ankle‐brachial index in antiphospholipid syndrome: Beyond the traditional risk factors. Issue 1 (10th July 2018) - Caraiola, Simona; Jurcut, Ciprian; Dima, Alina; Jurcut, Ruxandra; Baicus, Cristian; Baicus, Anda
Abstract : Introduction: The patients with antiphospholipid syndrome (APS) associate an increased risk of atherosclerosis. Objective: To determine the predictors of an abnormal ankle‐brachial index (ABI), surrogate measure of atherosclerosis, in patients with APS. Methods: The ABI was measured according to standard recommendations in 106 patients. Traditional cardiovascular risk factors were assessed in all cases. A large spectrum of APS antibodies was determined in 73 patients. Results: A total of 106 patients diagnosed with APS were included. 28.3% patients included were found to have low ABI. Anti‐beta 2‐glycoprotein I (aβ2GPI) IgG antibodies [4.00 (1.00‐79.00) vs 3.00 (0.00‐29.00) U/mL, P = 0.02] and antiprothrombin (aPT) IgM antibodies [4.50 (0.00‐82.00) vs 3.00 (0.00‐14.00) U/mL, P = 0.05] titers were found to be higher in patients with abnormal ABI. However, after multivariate regression analysis, only the aβ2GPI IgG titer remained predictor of low ABI ( P = 0.04). Conclusions: aβ2GPI IgG associated with impaired ABI in patients with APS. This relation might reflect their involvement in the atherosclerosis occurrence.